Interactions of bile acids and gut microbiota modulate neurological health: a comprehensive review on mechanisms and therapeutic potential of dietary phytochemicals - Wang, Jie; Zhang, Ying; Wu, Quan; Zhong, Yingfu; Xu, Ze; Yang, Juan (Frontiers in Microbiology, 2026)
Bile acids (BAs), classically regarded as detergents for dietary lipid absorption, have emerged as pivotal signaling molecules with systemic endocrine functions. The discovery of the Farnesoid X Receptor (FXR) and Takeda G protein-coupled receptor 5 (TGR5) as BAs-activated receptors unveiled their profound influences on glucose, lipid, and energy metabolism. BAs are first synthesized in hepatocytes and further metabolized by gut microbes, can either circulate in enterohepatic system or be found in circulations to exert various effects. More recently, the gut-brain axis has been identified as a critical pathway through which BAs exert significant effects on central nervous system (CNS) function and health. Based on research progresses mentioned above, this review systematically delineates the synthesis, metabolism, and classification of BAs, with a focus on the intricate crosstalk between the hepatic-gut BA axis and the brain. In addition, we explore the compelling evidences linking BAs dysregulation to a spectrum of neurological disorders, including neurodegenerative diseases (Alzheimer's and Parkinson's disease), depression, and hepatic encephalopathy. Besides, the potential mechanisms, such as alleviating neuroinflammation, maintaining the integrity of blood-brain barrier, increasing the neuronal survival, and modulating neurotransmitter systems are further elucidated. Finally, strategies of dietary intervention through phytochemicals to modulate the BAs pool for improved neurological outcomes are summarized and discussed. By integrating pre-clinical and clinical findings, this review aims to establish a foundation for understanding BAs as novel therapeutic targets in neurology and nutritional neuroscience.